Evolutionary design of conducting layers with fins and freedom. (November 2018) - Matsushima, H.; Almerbati, A.; Bejan, A.
Highlights: The access to flow is increased consistently by endowing the architecture with more freedom to change. Heat flow is facilitated by varying freely the thickness of the conducting wall. Heat flow is facilitated by varying freely the sizes, shapes and spacings of the fins. Heat flow access is facilitated even more by varying freely the wall and fins design. Abstract: Here we show that the morphology of a conducting wall can be 'evolved' by design so that its ability to enhance thermal contact with the ambient is maximized. Free to morph is the entire configuration of the conducting volume of the wall: the wall thickness and the population of fins planted on the wall are free to vary. The evolution of the design is pursued systematically. First, the thickness of the base layer is free to morph, and the population of fins is uniform (identical fins are spread equidistantly). Second, the base thickness and the fin-to-fin spacings are free to morph, while the fins are identical. Third, the base thickness and the fin sizes are free to morph, while the fins are distributed equidistantly. The emerging rules for distributing the wall thickness and the fin size and density are reported. The optimal allocation of the conducting material to the longitudinally conducting wall and the finned structure is also reported.